Hippocampal dysfunction provoked by mercury chloride exposure: evaluation of cognitive impairment, oxidative stress, tissue injury and nature of cell death - Aragão, Walessa Alana Bragança (2018)
Mercury (Hg) is a highly toxic metal, which can be found in its inorganic form in the environment. This form presents lower liposolubility and lower absorption in the body. In order to elucidate the possible toxicity of inorganic Hg in the hippocampus, we investigated the potential of low doses of mercury chloride (HgCl2) to promote hippocampal dysfunction by employing a chronic exposure model. For this, 56 rats were exposed to HgCl2 (0.375 mg/kg/day) via the oral route for 45 days. After the exposure period, the animals were submitted to the cognitive test of fear memory. The hippocampus was collected for the measurement of total Hg levels, analysis of oxidative stress, and evaluation of cytotoxicity, apoptosis, and tissue injury. It was observed that chronic exposure to inorganic Hg promotes an increase in mercury levels in this region and damage to short- and long-term memory. Furthermore, we found that this exposure model provoked oxidative stress, which led to cytotoxicity and cell death by apoptosis, affecting astrocytes and neurons in the hippocampus. Our study demonstrated that inorganic Hg, even with its low liposolubility, is able to produce deleterious effects in the central nervous system, resulting in cognitive impairment and hippocampal damage when administered for a long time at low doses in rats.